2008
DOI: 10.1017/s0144686x08007253
|View full text |Cite
|
Sign up to set email alerts
|

Can welfare-rights advice targeted at older people reduce social exclusion?

Abstract: It is known that, in general, people of pensionable age have gained in income compared to other age groups in the British population over the last two decades, but that a substantial minority still experience relative poverty. This paper reports a small qualitative study into the effectiveness of a welfare-rights advice and acquisition service for men and women aged 60 or more years that was provided through a local primary health-care service. Additional financial and non-financial resources were obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
1
39
0
2
Order By: Relevance
“…2001, Greasley 2003, Borland & Owens 2004, Greasley & Small 2005a,b, Moffatt et al. 2006a, 2010, Doncaster 2008, Moffatt & Scambler 2008).…”
Section: Resultsmentioning
confidence: 99%
“…2001, Greasley 2003, Borland & Owens 2004, Greasley & Small 2005a,b, Moffatt et al. 2006a, 2010, Doncaster 2008, Moffatt & Scambler 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the fact that conditional benefits were surrounded by moral debate was reflected in reported reluctance to apply for them, given the experienced or expected humiliations involved, as has been widely reported in other studies (Garthwaite, 2014, Salway et al, 2007, Moffatt and Higgs, 2007, Moffatt and Scambler, 2008.…”
Section: Conditionality Struggle and Non-entitlementmentioning
confidence: 87%
“…Sen (1995) outlined the potential negative effects of targeted benefits, including perverse incentives, dissuasion of uptake, and the stigmatising of recipients. As has been well documented Higgs, 2007, Moffatt andScambler, 2008), applying for conditional benefits is complex, and the administrative challenges are a deterrent to uptake. Older citizens may be particularly vulnerable to these threats.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence exists to substantiate these pathways. Existing research has demonstrated that advice services can lead to improvements in mental health and well‐being for recipients (Abbott, Hobby, Hobby, & Cotter, ; Burrows, Baxter, Baxter, Baird, Hirst, & Goyder, ; Citizens Advice Bureau, ; Hirst & Minter, ; Moffatt & Scambler, ). However, further research is required to test these pathways empirically, and to understand the underpinning mechanisms through which advice services generate these health outcomes.…”
Section: Introductionmentioning
confidence: 99%